John Tuzo Wilson (1908-1993) - Rowley, Graham; Rowley, Diana (ARCTIC, 1994)
With the death of Dr. John Tuzo Wilson on 15 April 1993, Canada lost a renowned scientist, and the North lost one of its most enthusiastic supporters. . At the outbreak of the Second World War, Jock joined the Canadian Army, proceeding overseas with the First Canadian Division in January 1940. He was recalled to Canada in 1943 to become the first director of Operational Research at National Defence Headquarters. Recognizing that Canada should play a leading role in the development of winter warfare, he organized a series of northern exercises. It was owing to his foresight and initiative that at the end of the war the Department of National Defence undertook Exercise Musk-Ox, which he directed. This major operation involved a journey in the winter and early spring of 1946 of more than 5000 kilometres through the Arctic and Subarctic by ten army oversnow vehicles, supported by RCAF aircraft. It was designed to test equipment and techniques developed during the war, particularly in relation to the part they might play in the civil evolution of the Canadian North. The success of this operation, which owed so much to his enthusiasm and able direction, had a far-reaching influence, both directly and indirectly, on the changes that have occurred in the Canadian North over the past half century. . Towards the end of the war Jock was one of a small group of Canadian and U.S. scientists who, recognizing the need for international cooperation in arctic science, founded the Arctic Institute of North America. He was the first chairman of its Board of Governors, and the first article in Arctic is under his name . Jock's guidance was often sought and valued by both national and international bodies, and it was readily given at all times. . [The number of honours and awards he received for his achievements are numerous.]